Stratégies d’intégration et de support en santé mentale des immigrants francophones au Canada anglais. - Archambault, Hélène; de Moissac, Daniel; Tempier, Raymond (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Résumé Cet article explore les stratégies d’intégration au système de santé telles que proposées par des personnes immigrantes francophones au sein de communautés francophones en situation minoritaire au Canada (CFSM). Une recherche qualitative par entrevues semi-dirigées a été menée dans trois villes canadiennes auprès de soixante personnes adultes immigrantes ou réfugiées. Centrées sur les représentations des personnes immigrantes quant aux services de soutien en santé mentale, diverses stratégies ont été dégagées. La préparation prémigratoire et le regroupement des informations sous un guichet unique semblent contribuer à une intégration réussie. L’appui des organismes communautaires et des autorités religieuses est bénéfique pour le soutien informationnel et socioémotionnel des nouveaux arrivants, ayant des retombées positives sur leur bien-être et leur capacité de s’intégrer à leur nouveau milieu de vie. Mots-clés : immigration, francophones, intégration, système de santé, stratégies Abstract This article explores healthcare integration strategies proposed by Francophone immigrants within Francophone minority communities (FMCs) in Canada. A qualitative study using semi-structured interviews was conducted in three Canadian cities with sixty adult immigrants and refugees. Focusing on immigrants’ perceptions of mental health support services, various strategies were identified. Pre-migration preparation and centralizing information seem to contribute to successful integration. The support of community organizations and religious authorities is beneficial for the socio-emotional and information support of newcomers, having a positive impact on their well-being and their ability to integrate into their new living environment. Keywords: immigration, Francophones, integration, healthcare, strategies

Patient and Provider Satisfaction With a Geomapping Tool for Finding Community Family Physicians in Ontario, Canada: Cross-Sectional Online Survey Study. - Belanger, Christopher; Peixoto, Cayden; Francoeur, Sara; Bjerre, Lise M. (JMIR formative research, 2024)
Background: Language-concordant health care, or health care in a patient’s language of choice, is an important element of health accessibility that improves patient safety and comfort and facilitates an increased quality of care. However, prior research has found that linguistic minorities often face higher travel burdens to access language-concordant care compared to the general population. Objective: This study intended to assess patient experiences and satisfaction with an online interactive physician map that allows patients to find family physicians who speak their preferred language in and around Ottawa, Ontario, Canada, as a means of identifying areas of improvement. Methods: This study used an online survey with questions related to user satisfaction. Responses to Likert-scale questions were compiled as summary statistics and short-answer responses underwent thematic analysis. The study setting was Ottawa and Renfrew County, Ontario, and the surrounding region, including the province of Quebec. Results: A total of 93 respondents completed the survey and self-identified as living in Ontario or Quebec. Overall, 57 (61%) respondents were “very satisfied” or “somewhat satisfied” with the map, 16 (17%) were “neither satisfied nor dissatisfied,” and 20 (22%) were “very dissatisfied” or “somewhat dissatisfied.” We found no significant differences in satisfaction by preferred language, age group, physician attachment, or intended beneficiary. A total of 56 respondents provided short-answer responses to an open-ended question about map improvements. The most common specific suggestion was to show which physicians are accepting new patients (n=20). Other suggestions included data refreshes (n=6), user interface adjustments (n=23), and additional languages (n=2). Some participants also provided positive feedback (n=5) or expressed concern with their inability to find a family physician (n=5). Several comments included multiple suggestions. Conclusions: While most patients were satisfied with the online map, a significant minority expressed dissatisfaction that the map did not show which family physicians were accepting new patients. This suggests that there may be public interest in an accessible database of which family physicians in Ontario are currently accepting new patients.

L’usage de technologies de santé pour accéder à des soins virtuels : une enquête exploratoire pour mieux comprendre les besoins et attentes des francophones de l’Ontario - Grosjean, Sylvie; Giguère, Lauriane; Lessard, Lysanne; Dionne, Émilie (Minorités linguistiques et société, 2024)
Dans cet article, nous présentons les résultats d’une étude visant à répondre à la question suivante : quels usages des technologies numériques de santé sont jugés accessibles et acceptables par les francophones de l’Ontario? Les résultats de cette enquête exploratoire montrent que l’accessibilité et l’acceptabilité des technologies de santé pour soutenir l’offre de soins virtuels chez les francophones de l’Ontario dépendent de plusieurs facteurs liés : a) à leur utilité perçue, b) à leur valeur sociale et leur intégration dans des usages existants, et c) à l’offre des technologies accessibles en français – de leur conception au support offert pour en accompagner les usages. Les résultats de l’étude nous invitent à considérer les questions à la fois communicationnelles (concordance linguistique patient/technologie), organisationnelles (intégration dans des pratiques et structures existantes) et éthiques qu’implique l’usage des technologies de santé visant à soutenir l’offre de soins virtuels pour les francophones de l’Ontario. Mots-clés : soins virtuels, technologies numériques de santé, acceptabilité, francophones, Ontario

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire à domicile - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2024)

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire à domicile (infographie) - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (2024)

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire en maison de retraite - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2024)

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire en maison de retraite (infographie) - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (2024)

Le Réseau à l’écoute. Rapport à la communauté 2022-2023. - Réseau des services de santé en français de l’Est de l’Ontario (2024)

Le Réseau à l’écoute. Rapport à la communauté 2023-2024. - Réseau des services de santé en français de l’Est de l’Ontario (2024)